Lunar Outpost The Challenges of Establishing a Human Settlement on the Moon - Seedhouse, Erik (Space Exploration, 2009)
Lunar Outpost provides a detailed account of the various technologies, mission architectures, medical requirements and training needed to return humans to the Moon within the next decade. It focuses on the means by which a lunar outpost will be constructed and also addresses major topics such as the cost of the enterprise and the roles played by private companies and individual countries. The return of humans to the surface of the Moon will be critical to the exploration of the solar system. The various missions are not only in pursuit of scientific knowledge, but also looking to extend human civilization, economic expansion, and public engagement beyond Earth. As well as NASA, China's Project 921, Japan's Aerospace Exploration Agency, Russia, and the European Space Agency are all planning manned missions to the Moon and, eventually, to Mars. The Ares-I and Ares-V are the biggest rockets since the Saturn V and there is much state-of-the-art technology incorporated into the design of Orion, the spacecraft that will carry a crew of four astronauts to the Moon. Lunar Outpost also describes the human factors, communications, exploration activities, and life support constraints of the missions.